Optimasi Multirespon Proses Permesinan EDM Sinking pada Material AISI P20 Menggunakan Metode Taguchi-Grey Relational Analysis - Ridhani Anita Fajardini; Dhika Aditya Purnomo; Farizi Rachman (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
Determining the combination of machining parameters is very important. The right machining parameters can produce optimal machining performance. EDM sinking is used to produce automotive components, aerospace, molds, and dies. AISI P20 is material that is widely used by manufacturing industry for dies and mold because of its hardness and resistance to heat. Based on these reasons, optimization is carried out to get appropriate parameter combination for the EDM sinking process using AISI P20. Process variables in this study are type of electrode, gap voltage, on time, and off time which aims to produce optimal response. Response variables observed were material removal rate, surface roughness, and electrode wear rate. Based on Taguchi method, matrix orthogonal L18 (21 × 73) was chosen for design of experiment. Taguchi method and Grey Relational Analysis used to optimize multiple responses simultaneously. Parameter optimum condition could be obtained by using graphite and setting values of gap voltage 50 volt, on time 250 ?s, off time 40 ?s. Percentage contribution of electrode type is 39,0733% whereas off time give contribution 32,4311%, on time 6,4574% and gap voltage 4,3590%.